Mutations in PpAGO3 Lead to Enhanced Virulence of Phytophthora parasitica by Activation of 25–26 nt sRNA-Associated Effector Genes - Xu, Junjie; Li, Yilin; Jia, Jinbu; Xiong, Wenjing; Zhong, Chengcheng; Huang, Guiyan; Gou, Xiuhong; Meng, Yuling; Shan, Weixing (Frontiers in Microbiology, 2022)
Oomycetes represent a unique group of plant pathogens that are destructive to a wide range of crops and natural ecosystems. Phytophthora species possess active small RNA (sRNA) silencing pathways, but little is known about the biological roles of sRNAs and associated factors in pathogenicity. Here we show that an AGO gene, PpAGO3, plays a major role in the regulation of effector genes hence the pathogenicity of P. parasitica. PpAGO3 was unique among five predicted AGO genes in P. parasitica, showing strong mycelium stage-specific expression. Using the CRISPR-Cas9 technology, we generated PpAGO3ΔRGG1-3 mutants that carried a deletion of 1, 2, or 3 copies of the N-terminal RGG motif (QRGGYD) but failed to obtain complete knockout mutants, which suggests its vital role in P. parasitica. These mutants showed increased pathogenicity on both Nicotiana benthamiana and Arabidopsis thaliana plants. Transcriptome and sRNA sequencing of PpAGO3ΔRGG1 and PpAGO3ΔRGG3 showed that these mutants were differentially accumulated with 25-26 nt sRNAs associated with 70 predicted cytoplasmic effector genes compared to the wild-type, of which 13 exhibited inverse correlation between gene expression and 25-26 nt sRNA accumulation. Transient over-expression of the upregulated RXLR effector genes, PPTG_01869 and PPTG_15425 identified in the mutants PpAGO3ΔRGG1 and PpAGO3ΔRGG3, strongly enhanced Nicotiana benthamiana susceptibility to P. parasitica. Our results suggest that PpAGO3 functions together with 25-26 nt sRNAs to confer dynamic expression regulation of effector genes in P. parasitica, thereby contributing to infection and pathogenicity of the pathogen.